Theoretical Aspects of Linguistic Research on Category of Space within Toponymy: From Observer Perception to Agent Motor Skills - A. I. Kopach (Научный диалог, 2025)
This paper addresses the issue of insufficient integration of human spatial exploration motor skills in the study of geographical names. A constructivist approach to the formation of toponymy as a cognitive domain for navigation is advocated. The illustrative material consists of names from all types of topographical objects across six historical and ethnographic zones of Belarus. It is demonstrated that the declarative nature of attention to toponyms with spatial semantics, along with the complexity of defining the meanings of geographical names, stems from an underestimation of the subject’s movement within significant spaces. The fundamental role of grammar in elucidating the meanings of toponymy and their interconnectedness within the cognitive domain is highlighted. The author emphasizes the adaptive role of consciousness in navigation, its orientation towards transcending local figure-ground relationships of objects, and constructing a spatial semantic network. It is asserted that the constitutive factor in forming an everyday toposystem is the positioning of objects relative to reference points in space that are significant for local residents, rather than isolated, narrowly localized situations involving pairs of locally connected realities. The paper presents the specifics of implementing systems of spatial reference in toponymy, identifying reference points within the toposystem and units of a foundational model for navigation, while also demonstrating the role of analogy in transferring the structure of units to names that convey non-spatial meanings.